Ідея єдності України крізь призму художніх публікацій на сторінках часопису «Промінь» (1922-1923 рр.) - Попович, Юлія Олександрівна (Інститут журналістики КНУ імені Тараса Шевченка, 2016)
The article reveals how the idea of the Ukrainisn integrity is refl ected in the literary works published on the pages of Chernivtsi literary and scientifi c journal “Promin» during 1922–1923. Attention is given to the complex of social and political conditions, to the censorship under the Romanian authorities in Bukovyna through which the Ukrainian word had to make its way in order to unite all the Ukrainian lands into a single independent state. The analysis involves the poetry and prose written by the well-known writers (such as P. Tychyna, D. Zahul, K. Polischuk, M. Pidhiryanka) and by the beginners also (such as M. Marfiyevych, O. Vilshyna, K. Lastivka). The main conclusion is as the following: «Promin» fi rmly stood on the positions of integrity in the period of statelessness of the Ukrainian nation, it took over the mission of defending national identity, and writers, breaking in their works problems common to all Ukrainian lands, accelerated the process of creating the Ukrainian state.
THE IDEA OF INTEGRITY OF UKRAINE THROUGH THE PRISM OF LITERARY PUBLICATIONS IN THE JOURNAL «PROMIN / BEAM» (1922–1923)
Keywords: unity, national idea, «Promin» («Beam»), periodicals of Bukovyna, poetry, prose; соборність, національна ідея, часопис «Про мінь», періодика Буковини, поезія, проза